Avaliações imunogenéticas do desenvolvimento de anticorpos inibidores do fator VIII na hemofilia A - Daniel Goncalves Chaves (2010)
Hemophilia A (HA) is a coagulopaty with hereditary transmission linked to Xchromosome resulting in a deficiency or a defect in coagulation factor VIII (FVIII). Subjects with this coagulopaty need constant FVIII infusions to sustain their hemostasis and physics integrity. During the treatment some patients develop an immune response that produces anti-FVIII antibodies. These antibodies, also called inhibitors, affect theprocoagulation activity of this protein and affect the treatment efficiency enhancing the costs and debilitate even further the patient. Despite the clinical relevance of factor VIII inhibitors to the impaired haemostatic activity of patients with HA, the exact immunological mechanisms underlying their production are still unknown. In this work, we designed and synthesized ten peptides whose sequences are found in epitopes at the surface of a1 and C2 domains of FVIII. All peptides were able to blockanti-FVIII Abs in plasma from patients. It was found an individual reactive profile to the peptides and this profile changed over the time. Three peptides were linked to a resine and an affinity chromatography assay was constructed to remove anti-FVIII Abs from plasma samples. Anti-FVIII IgGs were significantly captured by the peptide-Sepharose affinity matrixes as assessed by enzyme-linked immunosorbent assay.Haplotypes genotyping at the promotor region of IL-10 gene revealed associations with the FVIII inhibitors presence. The coexistence of a haplotype GCC that define high IL-10 synthesis and the haplotype ACC that confers intermediate production is associated with the group of patients who have a history of inhibitor development. Additionally,the coexistence of haplotypes defining high and low IL-10 syntheses is strongly associated with the lack of FVIII inhibitors in the plasma.Aiming to characterize the cytokine pattern in peripheral blood leukocytes from patients with [HA-FVIII(+)] and without [HA-FVIII(-)] anti-FVIII inhibitors, total blood samples were stimulated with pdFVIII or rFVIII. The results pointed out that decreased levels of TNF-+ neutrophils with higher IL-5/TNF- ratio is the hallmark of HA-FVIII(+). Despite all HA patients displayed decreased levels of IL-10+ monocytes, HA-FVIII(+) showed lower levels of TNF-+ monocytes, leading to an increase in theIL-10/TNF- ratio in this group. Analysis of adaptive immunity revealed that increased levels of IFN-+, TNF-+ and IL-4+ T-cells, from both CD4+ and CD8+ T-cells, are selectively observed in HA-FVIII(-). Moreover, increased frequency of IL-10+ B-cells and higher levels of -FVIII IgG1 were observed in HA-FVIII(-), whereas basal levels of cytokine+ B-cells and higher levels of -FVIII IgG4 are the major features of HA-FVIII(+). Additionally, the global cytokine profile demonstrated a predominance oftype-2 pattern in HA-FVIII(+), further sustained after the in vitro stimuli with pdFVIII or rFVIII. The polarized type-2 immune response in HA-FVIII(+) and the type-1 modulated in HA-FVIII(-) may be the key element controlling the development of inhibitory anti-FVIII antibodies. These findings may have implications for the enhancement or design of more safe and effective therapeutic protocols to control or to block inhibitors synthesis in HA patients.